A transparência semântica e memória de trabalho no processamento morfológico das palavras com o prefixo “des-” em português brasileiro - Silva, Danielli Cristina de Lima (2019)
Memory is of recognized importance for the retention of countless functions, with emphasis on the process of learning and retaining information to associate with new information that can be related to previous knowledge stored in it. We know many words that when used, both in speech and in reading and writing allow us to imagine that there is a form of storage that facilitates quick access. In studies in the field of word processing, questions about factors that lead to the recognition of morphologically complex words, including semantic transparency, are observed. In this sense, the interest arises as to whether semantic transparency would be related to a greater memory span in derived words. Therefore, we aim to investigate the relationship between semantic transparency and working memory of morphological structures / forms initiated by "des" with and without transparency. And as a specific objective, to discuss the conceptual aspects and classic problems of morphology; present a review of the literature on morphological studies in Brazilian Portuguese and other languages; compare memory span results in words beginning with "des". For that, two experiments were carried out. In the first we did a survey of trissílabos verbs initiated by "des", then we list the most frequent views through Linguateca's AC / DC project. With this, a form of Google was elaborated to consult, of the most frequent words listed, which would be the most familiar for adults between 18 and 30 years. For the second experiment, we had the span test in the Paradigm, in adults of 18 to 30 years, all graduate students and postgraduate studies from the Federal University of Paraíba, we use the most familiarity words, according to the result of experiment I, of which we have 40 words that were distributed in 4 conditions (transparent, semi-transparent, non-transparent and control), being applied in the Laboratory of Linguistic Processing - LAPROL / UFPB. Theoretically we support the design of language (gem) as innate capacity of Chomsky (1970), Garcia (2015), Kenedy (2016) among other researchers. In general, the results showed that the participants remembered a higher mean of words for the case of verbs in the condition of semantic transparency.